Renilla luciferase-based reporter assay for measuring autophagic flux - Farkas, Thomas (Methods Enzymol, 2017)
Macroautophagy (autophagy) is a dynamic intracellular degradation pathway. Monitoring the flux through the autophagy pathway is experimentally challenging but obviously a prerequisite for the proper investigation of the process. Here, we present an indirect autophagy flux assay based on monitoring the degradation of an autophagosome-associated fusion protein Rluc-LC3 by luminescence detection. The method is suitable for screening purposes with a high number of parallel samples and can be used for measurements in cell lysates as well as in living cells. The Rluc-LC3 assay has proven useful for the identification of genes, miRNAs and small molecules that regulate of autophagy flux in mammalian cells.